ผลของวิธีการสอนอ่านแบบเน้นกลวิธีที่มีต่อความสามารถด้านการอ่านภาษาอังกฤษและการรับรู้ความสามารถของตนเองด้านการอ่านของนักเรียนมัธยมศึกษาตอนต้น EFFECTS OF STRATEGY-BASED READING INSTRUCTION ON ENGLISH READING ABILITY AND READING SELF-EFFICACY OF LOW - มอนดี้, ดวงตา; ศุขะวาที, พรพิมล (An Online Journal of Education, 2014)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาผลของการสอนอ่านแบบเน้นกลวิธีที่มีผลต่อความสามารถด้านการอ่านของนักเรียน 2) ศึกษาผลของการสอนอ่านแบบเน้นกลวิธีที่มีผลต่อการรับรู้ความสามารถของตนเองด้านการอ่านของนักเรียน และ 3) ศึกษาความสัมพันธ์ระหว่างความสามารถด้านการอ่านและการรับรู้ความสามารถของตนเองด้านการอ่านของนักเรียน กลุ่มตัวอย่างประกอบด้วยนักเรียนชั้นมัธยมศึกษาปีที่ 3 ภาคเรียนที่ 2 ปีการศึกษา 2556 โรงเรียนกระเทียมวิทยา จังหวัดสุรินทร์ จำนวน 30 คน การทดลองใช้เวลาทั้งสิ้น 10 สัปดาห์ ได้รวบรวมข้อมูลเชิงปริมาณ โดยสถิติที่ใช้ในการวิเคราะห์คือ paired sample t-test และ correlation coefficient ผลการวิจัยพบว่า 1) คะแนนเฉลี่ยจากแบบทดสอบการอ่านหลังการทดลองของนักเรียนสูงกว่าคะแนนเฉลี่ยก่อนการทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ p<0.05 2) คะแนนเฉลี่ยจากแบบรับรู้ความสามารถของตนเองด้านการอ่านหลังการทดลองของนักเรียนสูงกว่าคะแนนเฉลี่ยก่อนการทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ p<0.05 และ 3) ความสามารถด้านการอ่านและการรับรู้ความสามารถของตนเองด้านการอ่านของนักเรียนมีความสัมพันธ์กันในระดับสูง ผลการวิจัยยังพบอีกว่านักเรียนทุกกลุ่มที่มีผลสัมฤทธิ์ด้านการอ่านแตกต่างกันมีคะแนนด้านการอ่านภาษาอังกฤษสูงขึ้นหลังการทดลอง โดยสรุปพบว่าการสอนอ่านแบบเน้นกลวิธีช่วยพัฒนาความสามารถด้านการอ่านภาษาอังกฤษและการรับรู้ความสามารถของตนเองด้านการอ่านภาษาอังกฤษของนักเรียนมัธยมศึกษาตอนต้น The objectives of this study were to: 1) investigate students’ reading ability improvement following the implementation of strategy-based reading instruction; 2) investigate the effects of the strategy-based reading instruction on students’ reading self-efficacy; and, 3) examine the relationship between students’ reading ability and reading self-efficacy. The sample consisted of 30 grade-9 students who were studying in semester 2 of the academic year 2013 at Krathiamwittaya School in Surin province. The experiment lasted 10 weeks. Data was analysed quantitatively using t-test and correlation coefficients. The results revealed: 1) for reading ability, students’ post-test mean score was significantly higher than that of the pre-test, at a level of p<0.05; 2) for reading self-efficacy, students had a significantly higher mean score from the post-questionnaire than from the pre-questionnaire at a level of p<0.05; and, 3) students’ reading ability and reading self-efficacy had a strong positive relationship. The results also showed that all groups of students from different reading achievement levels gained higher scores for their English reading ability following implementation. In conclusion, strategy-based reading instruction improved the reading ability and reading self-efficacy of lower secondary school students.